Implementasi Kebijakan Pemanfaatan Lahan untuk Perumahan dan Permukiman di Wilayah Kecamatan Pahandut di Kota Palangka Raya - Nurhasanah Nurhasanah; Imam Mahmud Abillah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to know, explain, describe the land utilization policy for housing and settlements in the river bank in Palangka Raya City. The type of research used is qualitative research methods. Where the techniques of collecting data through Obesevasi, in-depth interviews and documentation. Data analysis using quantitative data analysis, data reduction, data presentation and withdrawal of conclusions. The premier data in this study is the flamboyant SUB financial and community below. Based on the results of the study concluded that the implementation of land utilization policy for housing and settlements in the river bank in Palangka Raya city is still not maximal, that is because the communication has not been optimal, Funds to implement the policy has not been adequate, so to implement the policy has not been reached optimally. Advice that can be given to the people's housing department and the city settlements Palangka Raya in the Future SO (1) can further improve communication to the Community (2) increase the budget of funds to implement the mayor's meeting No. 8 In 2014 article 2 of land utilization